Microbiota-Gut-Brain Axis in Age-Related Neurodegenerative Diseases - Nie, Tong; You, Li; Tang, Fang; Duan, Yanhui; Nepovimova, Eugenie; Kuca, Kamil; Wu, Qinghua; Wei, Wei (Current Neuropharmacology, 2025)
BackgroundAge-related neurodegenerative diseases (NDs) pose a formidable challenge to healthcare systems worldwide due to their complex pathogenesis, significant morbidity, and mortality.Scope and ApproachThis comprehensive review aims to elucidate the central role of the microbiota-gut-brain axis (MGBA) in ND pathogenesis. Specifically, it delves into the perturbations within the gut microbiota and its metabolomic landscape, as well as the structural and functional transformations of the gastrointestinal and blood-brain barrier interfaces in ND patients. Additionally, it provides a comprehensive overview of the recent advancements in medicinal and dietary interventions tailored to modulate the MGBA for ND therapy.ConclusionAccumulating evidence underscores the pivotal role of the gut microbiota in ND pathogenesis through the MGBA. Dysbiosis of the gut microbiota and associated metabolites instigate structural modifications and augmented permeability of both the gastrointestinal barrier and the blood-brain barrier (BBB). These alterations facilitate the transit of microbial molecules from the gut to the brain via neural, endocrine, and immune pathways, potentially contributing to the etiology of NDs. Numerous investigational strategies, encompassing prebiotic and probiotic interventions, pharmaceutical trials, and dietary adaptations, are actively explored to harness the microbiota for ND treatment. This work endeavors to enhance our comprehension of the intricate mechanisms underpinning ND pathogenesis, offering valuable insights for the development of innovative therapeutic modalities targeting these debilitating disorders.
Keywords: Neurodegenerative diseases